Universal Ready-to-Use Immunotherapeutic Approach for the Treatment of Cancer: Expanded and Activated Polyclonal γδ Memory T Cells - Polito, Vinicia A.; Cristantielli, Rosaria; Weber, Gerrit; Del Bufalo, Francesca; Belardinilli, Tamascia; Arnone, Claudia M.; Petretto, Andrea; Antonucci, Laura; Giorda, Ezio; Tumino, Nicola; Pitisci, Angela; De Angelis, Biagio; et al. (Frontiers in Immunology, 2019)
Important progress has been registered in the last years in the treatment of patients suffering from oncological/haematological malignancies, but more still needs to be done to reduce toxicity and side-effects, improve outcome and offer new strategies for relapsed or refractory disease. A remarkable part of these clinical benefits is due to advances in immunotherapy. Here, we investigate the generation of a novel, universal and ready-to-use immunotherapeutic product based on γδ-T lymphocytes. These cells are part of the innate immune system exerting potent natural cytotoxicity against bacteria, viruses and tumours. This ability, coupled with their negligible alloreactivity, makes them attractive for adoptive immunotherapy approaches. To achieve a cell product suitable for clinical use, we developed a strategy capable to generate polyclonal γδ-T cells with predominant memory-Vδ1 phenotype and the additional possibility of gene-modification in good manufacturing practice (GMP) procedures. We expand clinically relevant numbers of functional polyclonal memory γδ-T cells under GMP conditions, with the additional possibility of gene-modification to improve anti-tumour activity. Irradiated engineered artificial antigen-presenting cells (aAPCs) expressing CD86/41BBL/CD40L and the cytomegalovirus (CMV)-antigen-pp65 have been used. The presence of CMV-pp65 and CD40L proved to be crucial for expansion of the memory-Vδ1 subpopulation. To allow clinical translation and guarantee patient safety, aAPCs were stably transduced with an inducible suicide gene. Expanded γδ-T cells showed high expression of activation and memory markers without signs of exhaustion, maintained polyclonality and potent anti-tumour activity both in vitro (with immortalized and primary blasts) and in vivo studies without allo-reactivity events. The molecular characterization (phophoproteomic and gene-expression) of these cell products underlines their unique properties. These cells can further be armed with chimeric antigen receptors (CAR) to improve anti-tumour capacity and persistence. We demonstrate the feasibility of establishing an allogeneic third-party, off-the-shelf and ready-to-use, γδ-T-cell bank. They represent an attractive therapeutic option endowed with broad clinical applications, including treatment of viral infections in highly immunocompromised patients by the presence of the memory Vδ1-subset, treatment of aggressive malignancies refractory to conventional approaches, bridging therapy to more targeted immunotherapeutic approaches and, ultimately, an innovative platform for the development of off-the-shelf CAR-T-cell products.